The impact of gratitude interventions on patients with cardiovascular disease: a systematic review - Wang, Xiaoxiao; Song, Chunli (Frontiers in Psychology, 2023)
Positive psychological factors play a pivotal role in improving cardiovascular outcomes. Gratitude interventions are among the most effective positive psychological interventions, with potential clinical applications in cardiology practice. To better understand the potential clinical effects of gratitude interventions in cardiovascular disease, four databases (Web of Science, Scopus, PubMed, and PsycArticles) were searched from 2005 to 2023 for relevant studies. Randomized controlled trials of gratitude interventions as the intervention and that reported physiological or psychosocial outcomes were eligible for inclusion. In total, 19 studies were identified, reporting results from 2951 participants from 19 to 71 years old from both healthy populations and those with clinical diagnoses. The studies showed that gratitude not only promotes mental health and adherence to healthy behaviors but also improves cardiovascular outcomes. Gratitude may have a positive impact on biomarkers of cardiovascular disease risk, especially asymptomatic heart failure, cardiovascular function, and autonomic nervous system activity.